The relationship of the science of jurisprudence with theology - jurisprudence and jurisprudence rules - Aljarallah, Jarallah Abdullah Ahmed (Journal of Islamic Sciences, 2024)
This research deals with the definition of the relationship between the science of the principles of jurisprudence with theology, jurisprudence and jurisprudence rules, in terms of the definition of each science linguistically and idiomatically, then the statement of the relationship of these sciences with the principles of jurisprudence, and the beginning is to mention the link between them, and then the statement of the difference.
Keywords: relationship; science of jurisprudence; theolog; science of jurisprudence rules